How Metallographic Examinations Can Give the Forming Process of Metal Artefacts? The Example of the Hoard Of Farébersviller - Cécile Veber; Michel Pernot (EXARC Journal, 2012)
The hoard of Farébersviller (Moselle, France) was discovered in 1991 during rescue excavations (See Image above). This set contains 130 "bronze" artifacts, which date to the Late Bronze Age (8th century BC). The technological study of the forming process consisted of three complementary approaches: detailed observations with a binocular microscope, secondly, revealing the alloy composition. Lastly a metallographic examination of samples was made to characterise the microstructure of the metal.